Developing Moral Sensitivity Through Protest Scenarios in International NGDOs’ Communication - Pinazo Calatayud, Daniel and Nos Aldas, Eloisa (Communication Research, 2016)
This article studies advertising campaigns of Nongovernmental Development Organizations (NGDOs) by applying the innovative concepts of protest communication scenarios and moral sensitivity. Its main purpose is to advance current understanding on how two conceptually different communication scenarios—donor and protest—impact the social engagement of the public. The interdisciplinary methodology combines a discursive and psychological perspective with an empirical survey study designed with the support of cultural discourse analysis. The findings demonstrate that using communication models based on the need for collective help for poverty in terms of an unjust situation—what we call a protest communication model—increases moral sensitivity and, therefore, social action. These results are of interest for planning and assessing the organizational communication of NGDOs designed from their educational and social action liabilities. This research shows that utilizing these criteria increases the efficacy of their communication in awareness raising and social engagement without being detrimental to funding amounts.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDkzNjUwMjEzNDkwNzIx